Peningkatan Kapasitas Komunikasi Pemasaran dan Kewirausahaan Digital Berbasis Artificial Intelligence (AI) pada Siswa Jurusan Kriya Kreasi Batik dan Tekstil SMKN 14 Bandung - Haris Annisari Indah Nur Rochimah; Rana Akbari Fitriawan; Amanda Bunga Gracia; Nanda Priatna; Syahira Malva Anadea; Fakhri Athar Radhian; Muhammad Akmal Irhamna (Arfah BHMS Foundation, 2026)
The regeneration of Indonesian batik artisans faces challenges in business sustainability and digital marketing development. As results from field observations of students majoring in Batik and Textile Creative Crafts at SMKN 14 Bandung show a gap between technical batik competencies and marketing communication competencies, foremost in narrating product values, identifying market, and building self-entrepreneurship capacity as Batikpreneurs. This phenomenon causes the inability of cultural creative products to compete in the digital ecosystem. The community service program entitled